Formation of atherosclerotic lesions is independent of eosinophils in male mice - Hofheinz, Katharina; Seibert, Fabian; Ackermann, Jochen; Dietel, Barbara; Tauchi, Miyuki; Oszvar-Kozma, Maria; Kühn, Hartmut; Schett, Georg; Binder, Christoph J.; Krönke, Gerhard (Atherosclerosis, 2020)
Background and aims: Oxidation of low-density lipoprotein (LDL) and oxidized LDL-mediated activation of the innate immune system have been recognized as early key events during the pathogenesis of atherosclerosis. Recent evidence identified eosinophils as a major source of enzymatic lipid oxidation and suggested a potential role of type 2 immunity in atherogenesis. However, the involvement of individual type 2 immune cell subsets involved in this process has been incompletely defined. We therefore sought to determine the role of eosinophils during LDL oxidation and the pathogenesis of this disease. Methods: Using eosinophil-deficient dblGATA1 mice, we studied the role of eosinophils in two established mouse models of atherosclerosis. Results: These experiments revealed that the presence of eosinophils did neither affect biomarkers of LDL oxidation nor atherosclerotic lesion development. Conclusions: The obtained results show that LDL oxidation and development of atherosclerosis are largely independent of eosinophils or eosinophil-mediated LDL oxidation.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Atherosclerosis; Eosinophils; Lipid oxidation